Axillary lymph node metastasis in gastrointestinal stromal tumor of jejunum: A case report - Bansal, Manishi; Gupta, Smriti; Gopal, Girdhar (Indian Journal of Case Reports, 2020)
A gastrointestinal stromal tumor (GIST) is the most common mesenchymal tumor of the gastrointestinal tract accounting for